2021
DOI: 10.3390/cancers13123019
|View full text |Cite
|
Sign up to set email alerts
|

NF-Y Subunits Overexpression in HNSCC

Abstract: NF-Y is the CCAAT-binding trimer formed by the histone fold domain (HFD), NF-YB/NF-YC and NF-YA. The CCAAT box is generally prevalent in promoters of “cancer” genes. We reported the overexpression of NF-YA in BRCA, LUAD and LUSC, and of all subunits in HCC. Altered splicing of NF-YA was found in breast and lung cancer. We analyzed RNA-seq datasets of TCGA and cell lines of head and neck squamous cell carcinomas (HNSCC). We partitioned all TCGA data into four subtypes, deconvoluted single-cell RNA-seq of tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Bezzecchi et al. used TCGA RNA-seq to analyze the HPV+ and HPV- Neck squamous cell carcinoma (HNSC) revealing that the overexpression of histone fold domain subunits and NF-YAs is counteracting cancer progression in HPV+ patients ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bezzecchi et al. used TCGA RNA-seq to analyze the HPV+ and HPV- Neck squamous cell carcinoma (HNSC) revealing that the overexpression of histone fold domain subunits and NF-YAs is counteracting cancer progression in HPV+ patients ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…We stratified the progression free interval—PFI—of STAD patients according to High, Intermediate, Low levels of NF-Y subunits expression. In addition, we considered the ratios of NF-YAl/NF-YAs, because this parameter was more informative than the overall levels of the two isoforms to predict patient outcomes in breast, lung and HNSCC cancers 25 27 , 29 . No correlation is scored according to the different levels of NF-YA and of the HFD subunits (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another study analyzing TCGA data found high expression of NF-YA, including of the protein in STAD specimens 31 ; this correlated with Cyclin E, a gene often amplified and overexpressed in STAD datasets 32 , 33 . These two studies did not report on the relative levels of the two major NF-YA subunits, which are clinically important in breast, lung and HNSCC cancers 25 27 , nor of the HFD subunits, which might be relevant in light on our recent finding on their overexpression in liver Hepatocarcinomas and HNSCC 28 , 29 . We report here on the analysis of STAD RNA-seq data present in TCGA, as further classified according to TCGA and ACRG.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Its location is 12q23.3. NFYB was highly expressed in multiple tumors and promotes tumor invasion, metastasis, and drug resistance [14][15][16]18]. However, the role of NFYB in gastric cancer has not been reported, so studying the effect of NFYB on GC may further clarify the possible mechanism of the occurrence and development of GC.…”
Section: Discussionmentioning
confidence: 99%